Determinants Of Muslim Consumers’ Purchase Intentions Toward Halal Food From Non-Muslim Producers: A Systematic Review - Haryanti, Peni; Al Idrus, Salim; Putra, Yuniarti Hidayah Suyoso (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study conducts a systematic literature review to explore the key factors influencing Muslim consumers’ purchase intentions toward halal food products manufactured by non-Muslim producers. A total of 42 empirical articles published between 2012 and 2024 were selected using PRISMA guidelines, drawn from databases such as Scopus, Web of Science, Emerald Insight, and ScienceDirect. Thematic analysis reveals five dominant factors: (1) perceptions of halalness and certification, (2) halal awareness and religiosity, (3) marketing strategies and brand image, (4) consumer trust in non-Muslim producers, and (5) socio-demographic variables as moderating elements. Findings show that while religiosity and halal awareness significantly shape intentions, trust in certification bodies and production transparency are critical in mitigating skepticism toward non-Muslim producers. Theoretically, this review extends the Theory of Planned Behavior by integrating context-specific variables, such as trust and religiosity, in the context of halal consumption. Practically, it offers strategic insights for non-Muslim companies entering the halal market, emphasizing the importance of segmentation, transparent communication, and collaboration with local Islamic institutions. Limitations and future research directions are also discussed, including the need for cross-cultural comparisons and longitudinal studies.